Iodine Biofortification of Apples and Pears in an Orchard Using Foliar Sprays of Different Composition - Budke, Christoph; Dierend, Werner; Schön, Hans-Georg; Hora, Katja; Mühling, Karl Hermann; Daum, Diemo (Frontiers in Plant Science, 2021)
Many people across the world suffer from iodine (I) deficiency and related diseases. The I content in plant-based foods is particularly low, but can be enhanced by agronomic biofortification. Therefore, in this study two field experiments were conducted under orchard conditions to assess the potential of I biofortification of apples and pears by foliar fertilization. Fruit trees were sprayed at various times during the growing season with solutions containing I in different concentrations and forms. In addition, tests were carried out to establish whether the effect of I sprays can be improved by co-application of potassium nitrate (KNO3) and sodium selenate (Na2SeO4). Iodine accumulation in apple and pear fruits was dose-dependent, with a stronger response to potassium iodide (KI) than potassium iodate (KIO3). In freshly harvested apple and pear fruits, 51% and 75% of the biofortified iodine was localized in the fruit peel, respectively. The remaining I was translocated into the fruit flesh, with a maximum of 3% reaching the core. Washing apples and pears with running deionized water reduced their I content by 14%. To achieve the targeted accumulation level of 50 - 100 µg I per 100 g fresh mass in washed and unpeeled fruits, foliar fertilization of 1.5 kg I per hectare and meter canopy height was required when KIO3 was applied. The addition of KNO3 and Na2SeO4 to I-containing spray solutions did not affect the I content in fruits. However, the application of KNO3 increased the total soluble solids content of the fruits by up to 1.0 °Brix compared to the control, and Na2SeO4 in the spray solution increased the fruit selenium (Se) content. Iodine sprays caused leaf necrosis, but without affecting the development and marketing quality of the fruits. Even after three months of cold storage, no adverse effects of I fertilization on general fruit characteristics were observed, however, I content of apples decreased by 20%.